The journal of Scott Pendleton Collins : a World War II soldier - Myers, Walter Dean (My name is America, 1999)
A seventeen-year-old soldier from central Virginia records his experiences in a journal as his regiment takes part in the D-Day invasion of Normandy and subsequent battles to liberate France.